Analisis Regresi Pengaruh Kemasan, Harga, dan Promosi Terhadap Keputusan Pembelian Kopi Wangi - Catur A. Pamungkas; Rusindiyanto Rusindiyanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Multiple regression analysis, Price, Packaging, Purchase decisions, Promotion. The fragrant coffee product is a coffee bean product from Excelsa coffee beans produced by PT In the marketing strategy carried out by PT The aim of this research is to improve the branding strategy for fragrant coffee products produced by PT This research collected data using a questionnaire with 5 Likert scales with an accidental sampling method of 100 respondents. The research methods used are multiple linear regression analysis, Kolmogorov test, heteroscedasticity test, multicollinearity test, linearity test using SPSS software. The research results obtained on the packaging variable have a value of 0.023<0.05 and the price variable has a value of 0.041<0.05, which means it has a significant influence on purchasing decisions. Meanwhile, the promotion variable has a value of 0.146>0.05, so it does not have a significant influence on the decision to purchase fragrant coffee products. This research also provides suggestions for overcoming problems found in the research.